Development of Tourism in Sumber Urip Village Kecamatan Selupu Rejang Rejang Lebong Regency - Nainggolan, Patma sari; utami, Anggun Dwi (Sumatra Journal of Disaster, Geography and Geography Education, 2020)
ABSTRACT:The purpose of this study was to identify internal and external factors of the Bukit Kaba Nature Tourism Park and Grojogan Sewu Hot Springs in Sumber Urip Village, Kecamatan Selupu Rejang, Rejang Lebong Regency. Formulate alternative strategies that are appropriate for the development of Bukit Kaba Nature Tourism Objects and Grojogan Sewu Hot Springs in Sumber Urip Village, Kecamatan Selupu Rejang, Rejang Lebong Regency. This type of research is qualitative research, the sampling technique uses non-probability with the type of snowball. The primary data collection process was carried out through interviews related to tourism development strategies in Sumber Urip Village, Kecamatan Selupu Rejang, Rejang Lebong Regency. Technical analysis in this study was SWOT Analysis. The results of this study are the description of the results of the SWOT analysis and strategies that can be used to realize it as a tourist area in Sumber Urip Village, Kecamatan Selupu Rejang, Rejang Lebong Regency (Study Object of Bukit Kaba Nature Park and Grojogan Sewu Hot Springs).